2020
DOI: 10.1021/acs.jafc.0c04041
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet Elicits Antitumor Properties through Inducing Oxidative Stress, Inhibiting MMP-9 Expression, and Rebalancing M1/M2 Tumor-Associated Macrophage Phenotype in a Mouse Model of Colon Cancer

Abstract: Many advanced cancers are characterized by metabolic disorders. A dietary therapeutic strategy was proposed to inhibit tumor growth through administration of low-carbohydrate, average-protein, and high-fat diet, which is also known as ketogenic diet (KD). In vivo antitumor efficacy of KD on transplanted CT26 + tumor cells in BALB/c mice was investigated. The results showed that the KD group had significantly higher blood β-hydroxybutyrate and lower blood glucose levels when compared with the normal diet group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 77 publications
0
40
0
Order By: Relevance
“…Moreover, our analyses revealed positive associations between FTL and FTH1 expressions and infiltration of both cell types in most cancers. Mounting evidence suggests that TAMs exhibit high plasticity and can switch between the anti-tumoral M1 subtype and the pro-tumoral M2 subtype, the latter of which is most abundant in solid tumors [ 41 , 42 ]. Ricolleau reported that FTL is mainly stored in M2-like TAMs in node-negative breast cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our analyses revealed positive associations between FTL and FTH1 expressions and infiltration of both cell types in most cancers. Mounting evidence suggests that TAMs exhibit high plasticity and can switch between the anti-tumoral M1 subtype and the pro-tumoral M2 subtype, the latter of which is most abundant in solid tumors [ 41 , 42 ]. Ricolleau reported that FTL is mainly stored in M2-like TAMs in node-negative breast cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, βhB inhibits the NFκB component of the pathway by binding GPR109A receptor [96,97], which the Montagne group found was sufficient to protect the BBB in ApoE4 mice [21]. Additionally, a ketogenic diet in mice was recently shown to inhibit HDAC, NFκB, and MMP9 expression [98].…”
Section: Ketogenic Diets and β-Hydroxybutyratementioning
confidence: 99%
“…Additionally, MMP-9 comprises the gelatinase sub-family of MMPs and is primarily produced by inflammatory cells and from the stromal cells surrounding a tumor or by the cancer cells themselves [146]. The use of ketogenic diet, in combination with other conventional cancer therapy, is expected to provide a noticeable reduction in the expression of MMP-9 in different types of cancer [142,147].…”
Section: Ketogenic Diet and Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%